Open governance and duality of technology: The open data designer-user disconnect in the PhilippinesRut - Cruz, Ruth Angelie B. (Animo Repository, 2019)
This paper builds on the data designer (government) and local data-user concepts in terms of “technological duality.” This model applies Orlikowski’s structurational model of tech- nology that extends basic ideas about interactions of organizations and information communica- tion technology (ICT). The model is supported by its application to multiple interpretative case studies of the Philippine Open Government initiative. It was evidenced that open government data as a technology is subjective—understood and interpreted inconsistently by the government and data users and therefore creates a disconnect between them. Based on the cases presented, it is proposed that a two-way open governance model will be a more effective approach in devel- oping a truly open government. This reinforces the role of user-side stakeholders as they have the interest, expertise, and resources to utilize open data and can therefore build networks with more users within their respective fields that government initiatives may not be able to reach.